(untitled) (Research, Society and Development, 2022)
Benzodiazepines are the most used anxiolytics for the treatment of some public health problems, especially by patients who receive assistance in CAPS, but they can have dangerous effects when taken improperly. Thus, the study aimed to evaluate the Brazilian context of availability and consumption of benzodiazepines, from the point of view of users of CAPS in the city of Teresina-PI, health professionals and the dispensing of these drugs. The research was carried out at CAPS in the municipality of Teresina-PI between August and September 2021. All results were supported by approval by the ethics committee of the UNINOVAFAPI university center, the information being collected through questionnaires sent via email or whatsapp . As a profile, there was a majority of women aged 51 to 62 years, single, complete elementary school and with 3 other members in the household. As for the reasons for starting to use medication, the combination of anxiety, depression and insomnia was observed in 66.2% of patients. There was a majority of clonazepam consumption by patients among benzodiazepines. Overall, the dosage of 2mg once a day in the evening or at night was the most used dosage. Modification of the use or withdrawal of medication from patients was also observed, this measure being often taken by the user, without medical recommendation.